PROJECTION IN DIALOGUE ROMEO AND JULIET SHAKESPEARE’S - Tasya Ahbanni (Linguistik, Terjemahan, Sastra (LINGTERSA), 2022)
This thesis studies projection in the complex clauses which are found in Shakespeare’s Romeo and Juliet dialogue. The aims of this study are (1) to find out the types of projection in Shakespeare’s Romeo and Juliet dialogue, and (2) to find out the realization of projections in Shakespeare’s Romeo and Juliet dialogue based on the data that have been analyzed in line with the theory of projection. The data of this study were clause complexes found in Shakespeare’s Romeo and Juliet dialogue. This research is conducted by using a descriptive qualitative approach. The data are analyzed by using the Systemic Functional Linguistics (SFL) theory. The result shows that in (1) In Shakespeare’s Romeo and Juliet dialogue, four types of projection were found, there were 55 clauses complexes of projection. Of the four types of projection that occurred, the highest number of occurrences is Paratactic Locution for 40 clauses (72,7%), followed by Hypotactic Locution for 8 clauses (14,5%), Paratactic Idea for 5 clauses (9,1%), and 2 clauses (3,7%) of Hypotactic Idea. (2) The realization of projection in Shakespeare’s Romeo and Juliet dialogue in terms of verbal locutions and mental ideas. The verbal locution consists of 40 clause complexes for Paratactic Locution, and 8 clause complexes for Hypotactic Locution whereas the mental idea consists of 5 clause complexes for Hypotactic Idea and, 2 complex clauses for Paratactic Idea.